CO2 enrichment and soil type additively regulate grassland productivity. Issue 1 (23rd November 2018) - Polley, H. Wayne; Aspinwall, Michael J.; Collins, Harold P.; Gibson, Anne E.; Gill, Richard A.; Jackson, Robert B.; Jin, Virginia L.; Khasanova, Albina R.; Reichmann, Lara G.; Fay, Philip A.
Summary: Atmospheric CO2 enrichment usually increases the aboveground net primary productivity (ANPP) of grassland vegetation, but the magnitude of the ANPP–CO2 response differs among ecosystems. Soil properties affect ANPP via multiple mechanisms and vary over topographic to geographic gradients, but have received little attention as potential modifiers of the ANPP–CO2 response. We assessed the effects of three soil types, sandy loam, silty clay and clay, on the ANPP response of perennial C3 /C4 grassland communities to a subambient to elevated CO2 gradient over 10 yr in Texas, USA. We predicted an interactive, rather than additive, effect of CO2 and soil type on ANPP. Contrary to prediction, CO2 and soil additively influenced grassland ANPP. Increasing CO2 by 250 μl l −1 increased ANPP by 170 g m −2 across soil types. Increased clay content from 10% to 50% among soils reduced ANPP by 50 g m −2 . CO2 enrichment increased ANPP via a predominant direct effect, accompanied by a smaller indirect effect mediated by a successional shift to increased dominance of the C4 tallgrass Sorghastrum nutans . Our results indicate a large, positive influence of CO2 enrichment on grassland productivity that resulted from the direct physiological benefits of CO2 augmented by species succession, and was expressed similarly across soils of differing physical properties.